Primitivism and Identity in Latin America : Essays on Art, Literature, and Culture - González, Jose Eduardo; Camayd-Freixas, Erik (Book collections on Project MUSE., 2000)
"Examining such subjects as Julio Cortazar and Frida Kahlo and such topics as folk art and cinema, the volume brings together for the first time the views of scholars who are currently engaging the task of cultural studies from the standpoint of primitivism. These varied contributions include analyses of Latin American art in relation to social issues, popular culture, and official cultural policy; essays in cultural criticism touching on ethnic identity, racial politics, women's issues, and conflictive modernity; and analytical studies of primitivism's impact on narrative theory and practice, film, theater, and poetry."--Jacket.